KONTRIBUSI KETERAMPILAN MEMBACA PEMAHAMAN TEKS DESKRIPSI TERHADAP KETERAMPILAN MENULIS TEKS DESKRIPSI SISWA KELAS VII SMP NEGERI 1 BAYANG UTARA - Srimelisa, Defni; Thahar, Harris Effendi; Arief, Ermawati (Universitas Negeri Padang, 2019)
ABSTRACTÂ The porpose of this research there are three. First, to describes the skills of reading comprehension text description grade VII SMP Negeri 1 Bayang Utara. Second, to describes a text description of the writing skills of students grade VII SMP Negeri 1 Bayang Utara. Third, describing the contribution of the intermediate reading comprehension text descriptions against writing skills text description grade VII SMP Negeri 1 Bayang Utara.Â This research type is quantitative descriptive method. The design used in this research is the design contribution. This research population is grade VII SMP Negeri 1 Bayang Utara that are listed in the 2017/2018, i.e., 268 students. The sample in this research are determined by proportional random sampling of 15% of the population, i.e. 40 students. Research data is a score test results intermediate reading comprehension text description and score the writing skills test result text description. Research instrument is an objective test to measure the skills of reading comprehension text description and performance tests to measure the skills of writing a text description. The results of the research there are three. First, a text description of the writing skills of students of grade VII SMP Negeri 1 Bayang Utara lies on the qualifications of either (B). Second, the skills of reading comprehension text description grade VII SMP Negeri 1 Bayang Utara are on Good qualifications (B). Third, intermediate reading comprehension text descriptions account for 47.20% against writing skills text description grade VII SMP Negeri 1 Bayang Utara.Â Kata kunci: Kontribusi, Membaca Pemahaman, Menulis, Teks Deskripsi